Customary Justice Model in Resolving Indigenous Conflicts in Merauke Regency Papua - Erni Dwita Silambi; Marlyn Jane Alputila; Syahruddin Syahruddin (Musamus Law Review, 2018)
The background of the keyword is the agenda of customary justice in the government which is clearly burdened by rules that are recognized and carried out well, making it possible to provide recognition of the prevailing customs in the community. The "confession" here is formal approval. The focus of the research is the implementation of customary justice in Papua in terms of Law Number 21 Year 2001 concerning Special Autonomy for Papua. The research objective is to design or formulate a model of customary justice in Papua. The target of the study is to get the right model of customary justice that is understood in their decisions in solving problems that occur in Papua. Merauke.Metote research in this research is qualitative research. The research conducted is learning, literature, taking data and interviews in depth. After that the data obtained are described and analyzed with quantitative methods to formulate economic empowerment models. The results of this study are the existing customary models, so that in the context of customary cases there are also cases where adat cases can be issued by the community.